THE ESSENCE OF THE SYSTEM-ACTIVITY APPROACH AND CRITICAL THINKING IN THE EDUCATIONAL PROCESS - Кумарбекулы, Санат; Абдиманапов, Бахадурхан; Усенов, Нурбол; Женсикбаева, Назгуль (Pedagogy and Psychology, 2021)
The article describes the structure, content and role of the system-activity approach in the development of critical thinking among students of educational institutions. The definition of the concept of "system-activity approach" is given, its main components and principles of implementation of the approach in scientific activity are highlighted. As you know, a modern student should have the skills to independently search for new knowledge, process and analyze it, develop new skills and abilities in accordance with educational goals, distinguish and independently find ways to solve existing problems, creatively approach the solution of educational goals and tasks. In the conditions of modern education, students often have to solve non-standard educational tasks in conditions unfamiliar to them, where the method of teaching schoolchildren in accordance with the requirements of a system-activity approach – as problem-based learning plays an essential role in their solution. It should be noted that as the main technological. the component of the system-activity approach becomes the condition of the actual activating difficulty, where the final result is an individual educational result obtained in the course of students' conscious learning activities. The result of this work can be put forward ideas, hypotheses, versions and methods obtained in the results of students' activities (schemes, models, experiments, texts, projects, etc.). All this is one of the key differences between the system-activity approach from traditional (knowledge) methods in teaching. Critical thinking has its own characteristics, its own conceptual system that distinguish it from other types and types of thinking. In most cases, we consider critical thinking only in relation to other types of thinking, in combination and comparison with such concepts as productive, problematic, creative, logical and systemic thinking, intelligence and with other concepts of active, purposeful mental and practical human activity. The paper analyzes the scientific approaches of foreign scientists in defining the concepts of "system-activity approach" and "critical thinking".